258WS Evidence to recommendations frameworks: Diagnosis. (15th August 2013) - Schünemann, H; Alonso, P; Bossuyt, P; Brozek, J; Leeflang, M; Deurenberg-Gopalakrishna, G; Langendam, M; Koster, M; Mustafa, R; Santesso, N
Abstract : Background: Moving from evidence to recommendations (EtR) in guideline development requires balancing evidence quality with the benefits and harms of interventions, patient preferences, and resource and cost considerations. Developing recommendation about diagnostic tests and strategies is particularly challenging and requires tackling complex challenges, different than those needed for therapeutic interventions. The GRADE Working Group, has developed an approach to integrate these factors into development of clinical practice recommendations that is currently further defined in the DECIDE (Developing and Evaluating Communication Strategies to Support Informed Decisions and Practice Based on Evidence) project. This workshop will introduce this approach and evaluate the EtR framework based on examples and hands-on exercises. Objectives: To learn how to use and evaluate the EtR framework for diagnostic questions. Target Group, Suggested Audience: Guideline developers, systematic reviewers, clinicians. Description of the Workshop and of the Methods used to Facilitate Interactions: This workshop provides a brief didactic overview of GRADE for diagnostic questions. Each group will use a systematic review and a partially pre-filled EtR framework. During the small group work, participants will discuss challenges and advantages of the approach. Participants will then apply these concepts in small groups to develop a recommendation based on the workshop material; there will be a plenary to provide feedback that will help to enhance the work and provide opportunities for collaboration.